Sufistic Hermeneutics: the Construction of Ibn Arabi's Esoteric Interpretation on the Process of Becoming Insan Kamil - Mukhtar, Mukhtar; Hamzah, Hamzah; Mahmud, Basri (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2023)
This study aims to determine the style of interpretation of Ibn Arabi in interpreting the immanence of God in human form so that humans get the position of insan kamil. The method used in this research is the descriptive analytical method, which is an analytical description of the construction of esoteric interpretation from a hermeneutic perspective. Primary data refers directly to the thoughts and writings of Ibn Arabi.In contrast, secondary data comes from supporting reference sources in the form of books, books, and articles about Ibn Arabi, who interprets Ibn Arabi's interpretation related to his understanding of the texts of the Qur'an. The approach used is a hermeneutic philosophical approach, a Sufistic approach, and an interpretation approach. Researchers use the hermeneutic philosophical approach to discover the fundamental structure of Ibn Arabi's thoughts and what influences their background. In comparison, the Sufistic approach is used because the reconstruction of Ibn Arabi's perspective cannot be separated from the Sufistic approach. The interpretive approach is used because this research study has relevance to the interpretation of which the nuances of the interpretation have an isyari pattern. The results of this study, through the approach of Ibn Arabi's esoteric interpretation, implicitly found that Ibn Arabi approached the texts of the Qur'an by using ta'wil, an interpretation model that goes beyond the outward meaning of the text of the Qur'an. This pattern of interpretation can be observed in his interpretation of the path to becoming Insan Kamil. Ibn Arabi describes the side humans possess, namely tajalli; God manifests His transcendent self in outward forms through His attributes and names. Human perfection in this aspect is only potential. According to Ibn Arabi, to become Insan Kamil, humans actualize that potential to the highest awareness until they realize their unity with God. Hermeneutika Sufistik: Konstruksi Tafsir Esoterik Ibnu Arabi Tentang Proses Menjadi Insan Kamil. Penelitian ini bertujuan untuk mengetahui corak penafsiran Ibn Arabi dalam menafsirkan imanensi Tuhan dalam wujud manusia, sehingga manusia mendapatkan posisi Insan Kamil. Adapun metode yang digunakan dalam penelitian ini adalah metode deskriptif analitis yaitu penggambaran secara analitis konstruksi dari tafsir esoteric dalam perspektif hermenetik. Data primernya adalah data-data yang merujuk langsung pada pemikiran dan tulisan Ibn Arabi, sedangkan data sekundernya adalah data-data yang berasal dari sumber referensi pendukung baik dalam bentuk buku, kitab maupun artikel tentang Ibn Arabi yang mengiterprertasikan tafsiran Ibn Arabi terkait dengan pemahamannya terhadap teks-teks al-Qur’an. Adapun pendekatan yang digunakan adalah pendekatan filosofis hermeneutik, pendekatan sufistik dan pendekatan tafsir. Pendekatan filosofis hermeneutik digunakan oleh peneliti untuk mencari tahu struktur fundamental pemikiran-pemikiran Ibn Árabi dan yang mempengaruhi latar belakangnya. Sedangkan Pendekatan sufistik digunakan sebab rekonstruksi cara pandang Ibn Arabi tidak bisa terlepas dari pendekatan sufistik. Adapun pendekatan tafsir digunakan sebab kajian penelitian ini memiliki relevansi dengan tafsir yang nuansa tafsirnya bercorak isyari. Hasil penelitian ini melalui pendekatan tafsir esoterik Ibn Arabi, secara implisit ditemukan bahwa Ibn Arabi mendekati teks-teks al-Qur’an dengan menggunakan ta’wil, yaitu model penafsiran yang melampaui makna lahiriah teks al-Qur’an. Corak penafsiran ini dapat dicermati dalam tafsirannya tentang jalan menjadi Insan Kamil. Ibn Arabi menggambarkan sisi yang dimiliki oleh manusia, yaitu tajalli; Tuhan memanifestasikan diri-Nya yang transenden dalam wujud-wujud lahiriyah lewat sifat dan nama-Nya. Kesempurnaan manusia dalam sisi ini hanyalah bersifat potensial, sehingga menurut Ibn Arabi untuk menjadi Insan Kamil sejatinya manusia mengaktualisasikan potensi tersebut sampai pada kesadaran tertinggi sampai menyadari kesatuannya dengan Tuhan.